Contemporary Challenges to Constitutionalism - Suchocka Hanna (Baltic Journal of Law & Politics, 2025)
This article examines the development and abusive use of constitutionalism in Central and Eastern Europe following the post–communist transitions of the 1990s. While new constitutions initially aligned with European standards and values, recent trends reveal a growing misuse of constitutional tools by dominant political forces. The text highlights the role of the Venice Commission and the fragility of democratic institutions. It argues for the importance of constitutional culture, judicial independence and dialogue to prevent the instrumentalization of constitutions for political ends.